Corporate financial analysis in a global environment - Harrington, Diana R (Australia South-Western College, 2000)
Corporate Financial Analysis was written with the objective of discusing financial analysis as it relates to managerial decision making and exchange business performance.The author also discusses international financial statements and the financial impact
Keywords: Corporations-Finance